Dynamic capabilities framework and its transformative contributions - Cavusgil, S. Tamer; Deligonul, Seyda Z. (Journal of International Business Studies, 2025)
Dynamic capabilities refer to an organization’s ability to integrate, build, and reconfigure internal and external competencies to address a rapidly developing environment. In his highly influential 2014 JIBS paper, David Teece provides a holistic explanation of how firms can: achieve sustained competitive advantage, adjust and preserve superior performance, and adapt to changing environments. The article, along with Teece’s related contributions, is remarkable in that it has led us to rethink and reframe our conventional understanding of markets, strategy, competitive advantage, and the firm. In this commentary, we reflect on the transformative contributions of the article. We argue that the dynamic capabilities framework provides a foundation for theorizing and developing a coherent logic that guides theory development.